MODIFIED LQ AND DYNAMIC ECONOMIC BASE (Fokus Ekonomi, 2011)
Economic Base is an important concept in the regional development planning. This paperconsists of three parts; theory, analytical tool and case studies of regional economic base. Firstly,we review the theory and various empirical measures of economic base. Location Quotient (LQ) iscommonly used in the empirical works in regional economic planning i.e. economic base.Secondly, we point out some shortcomings in LQ as an analytical tool for economic base. Basedon works of Vollrath (1991), Laursen (1998) and Dalumn et al (1998), Wörz (2005), we propose amodified version of LQ, namely symmetric LQ (SLQ), which is suitable for analyzing dynamicspecialization using econometric models. Thirdly, we apply the analytical tool to analyze thedynamics of economic base in the cases of districts in Special Region of Yogyakarta, Indonesia.Key words: Symmetric Location Quotient, Dynamic Economic Base. JEL Classification: R10; R11, R12.